The Polar Cultural Heritage as a Tourism Attraction: A Case Study of the Airship Mooring Mast at Ny-Ålesund, Svalbard - Roura, Ricardo (Téoros)

(untitled) (Université du Québec à Montréal, 2009)
This paper explores the use of narratives in the transformation of historic sites in the polar regions into attractions and consumable tourism products. The analysis is based on a case study of visitation to the airship mooring mast built at Ny-Ålesund, Svalbard, for the 1926 “Amundsen-Ellsworth-Nobile Transpolar Flight” of the airship Norge. The questions addressed in this paper are: How does cultural heritage in the polar regions operate as a tourist attraction? What is the role of tourism narratives in creating a tourism attraction? Direct observations constituted the main research method. Based on Dean MacCannell (1976) and Neil Leiper (1990), a tourism attraction is a system comprising a tourist or human element; a nucleus or central element; and a marker or informative element. Tourism narratives enable the different elements of the tourism attraction system to “click” together into a coherent whole. Through narratives, the mast becomes a place of significance and a symbolic marker of the North Pole and polar exploration. The application of this approach to other sites in Antarctica and Svalbard is discussed.